PENGARUH DANA PIHAK KETIGA, MARGIN KEUNTUNGAN, SERTIFIKAT WADIAH BANK INDONESIA, RETURN ON ASSET, DAN NON PERFORMING FINANCING TERHADAP PEMBIAYAAN MURABAHAH PADA BANK SYARIAH MANDIRI DAN BANK MUAMALAT INDONESIA PERIODA 2009-2013 - Rizqi Amalia; Khusnul Hidayah (Universitas Ahmad Dahlan, 2015)
Islamic banks have the same functionality conventional banks as intermediaries of financial services (financial intermediary), has a fundamental duty to collect funds from the public and channeled back to the community in the form of financing facilities. Fund raising is done through savings and investments such, wadiah deposits, savings and time deposits. The distribution of funds is done with some kind of contract as, murabahah, istishna, mudharabah, musyarakah, ijarah, and salam. The purpose of this research is to determine the effect of Third party funds (DPK), profit margin, wadiah certificate of Indonesian Bank (SWBI), return on assets (ROA), and non performing financing (NPF) to murabahah financing. Object in the reserach is Bank Syariah Mandiri and Bank Muamalat Indonesia period 2009-2013. The result of analysis showed by simultan DPK, profit margin, SWBI, ROA, and NPF effect to murabahah financing. Predictive ability of the five variables to financing is 98.7% which is indicated by the amount of adjusted R2 and the rest is influenced by other variables. DPK, and ROA partially positive effect to murabahah financing. SWBI negatively affect to murabahah financing. The profit margin is not a positive influence to murabahah financing and NPF does not negative affect to murabahah financing.